Cholinergic Modulation of General Anesthesia - Leung, Lai-Wo S.; Luo, Tao (Current Neuropharmacology, 2021)
Acetylcholine in the brain promotes arousal and facilitates cognitive functions. Cholinergic neurons in the mesopontine brainstem and basal forebrain are important for activation of the cerebral cortex, which is characterized by the suppression of irregular slow waves, an increase in gamma (30- 100 Hz) activity in the electroencephalogram, and the appearance of a hippocampal theta rhythm. During general anesthesia, a decrease in acetylcholine release and cholinergic functions contribute to the desired outcomes of general anesthesia, such as amnesia, loss of awareness and consciousness, and immobility. Animal experiments indicate that inactivation, lesion, or genetic ablation of cholinergic neurons in the basal forebrain potentiated the effects of inhalational and injectable anesthetics, including isoflurane, halothane, propofol, pentobarbital, and in some cases, ketamine. Increased behavioral sensitivity to general anesthesia, faster induction time, and delayed recovery of a loss of righting reflex have been observed in rodents with basal forebrain cholinergic deficits. Cholinergic stimulation in the prefrontal cortex, thalamus, and basal forebrain hastens recovery from general anesthesia. Anticholinesterase accelerates emergence from general anesthesia, but with mixed success, in part depending on the anesthetic used. Cholinergic deficits may contribute to cognitive impairments after anesthesia and operations, which are severe in aged subjects. We propose a cholinergic hypothesis for postoperative cognitive disorder, in line with the cholinergic deficits and cognitive decline in aging and Alzheimer’s disease. The current animal literature suggests that brain cholinergic neurons can regulate the immune and inflammatory response after surgical operation and anesthetic exposure, and anticholinesterase and α7-nicotinic cholinergic agonists can alleviate postoperative inflammatory response and cognitive deficits.
Keywords: nucleus basalis